Strain engineering in graphene by laser irradiation - Papasimakis, N. (2015)
We demonstrate that the Raman spectrum of graphene on lithium niobate can be controlled locally by continuous exposure to laser irradiation. We interpret our results in terms of changes to doping and mechanical strain and show that our observations are consistent with light-induced gradual strain relaxation in the graphene layer.